Оптическая спектроскопия фторида кальция с пространственно-временным разрешением; Известия вузов. Физика; Т. 58, № 6 (2) - Штанько В. Ф. Виктор Федорович; Степанов С. А. Сергей Александрович; Иванова Т. С. Татьяна Сергеевна; Чинков Е. П. Евгений Петрович (2015, 2015)
Заглавие с экрана